Migrants, Borders and the European Question - Nahaboo, Zaki. author. aut Link
VIII, 97 p. 1 illus.
Keywords: “Nahaboo and Kerrigan make a timely intervention into discussions of the 'European Question' and our understanding of race, space, bordering and refugeehood in the context of the Calais Jungle. This important work will be of interest to scholars and students thinking through questions of migration via an interdisciplinary lens as they bring together theories and experiences of Geography, History, Sociology, Politics and IR in this important and fascinating new work.” —Gemma Bird, Senior Lecturer in Politics and International Relations, University of Liverpool, UK “Nahaboo and Kerrigan’s rich analysis of the ‘Calais Jungle’ as a site of racialised exceptionality, contested rights and love provides fascinating insights into the ever-thorny ‘European Question.’” —Vicki Squire, Professor of International Politics, University of Warwick, UK 'Nahaboo and Kerrigan provide a compelling account of the violent spatial and racialised logics that shape the Calais ‘Jungle’. Refusing to posit this camp as an aberration of contemporary migration governance, they reveal how the production of destitution and misery is not only purposeful but central to the fabric of European postcoloniality. Whilst providing insightful analysis of the legacies of empire in Calais and beyond, the book accounts for the possibility of resistance and hope amongst the turmoil of seeking asylum in an ever more bordered world.' —Joe Turner, Lecturer in Politics, University of York, Author of Bordering Intimacy: Postcolonial Governance and the Policing of Family, Manchester University Pres This book examines how the Calais Jungle posed and addressed the European Question. The issue of who and what counts as European was articulated through this makeshift camp. The book argues that the Jungle acquired meaning as a localised struggle to defineterritory, borders, rights and refugees in Europe. Henri Lefebvre’s spatial triad is used as a framing device for analysis. Discourses of tropicality are shown to produce the Jungle in terms of a postcolonial space of exception. This representational space fused bodies and environment in racialised ways. Attention is then drawn to assemblages that gave rise to political subjectivity, which partially elided a Eurocentric prism of rights. Here, the book explores how a ‘right to the jungle’ was generated via relations between refugees, aid workers and material objects—constituting the Jungle as a space of representation. Finally, intimate life in, and beyond, the Jungle is examined as a spatial practice that contests the EU border regime. Zaki Nahaboo is a lecturer in sociology at Birmingham City University, UK. He has research and teaching interests in postcolonial studies, historical sociology, and international political sociology. Zaki writes about imperial citizenship, the racialization of migration, free speech, and multiculturalism. Nathan Aaron Kerrigan is a lecturer in sociology at Birmingham City University, UK. Nathan's teaching and research interests centre around themes of community, space, and place. He is particularly interested in the way these different thematic areas impact on the regulation and control of minority ethic and migrant bodies in rural areas. .